KEEFEKTIFAN MEDIA PEMBELAJARAN LINE CONVERTER DALAM MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS III SD - Nofi Kristianto; Ardhi Prabowo; Decky Avrilianda; Nuni Widiarti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop and analyze the effectiveness of a ruler learning media for converting units of length, called "Line Converter" in improving mathematics learning outcomes of third-grade students at Gedangdowo 2 Public Elementary School, especially on the topic of relationships between units of length. The background of this study is the existence of problems related to the lack of interactive mathematics learning media, teachers' learning strategies that are still conventional, low levels of student activity and enthusiasm in learning, and suboptimal mathematics learning outcomes. This study aims to present a comprehensive analysis through a Systematic Literature Review (SLR) approach to 38 scientific articles published in 2023–2026. The results of the analysis show that approximately 82% of studies reported a significant increase in students' understanding and learning outcomes about converting units of length. The results of this study are expected to produce valid, practical, and effective Line Converter media to improve student learning outcomes. In addition, this study is also expected to contribute to the development of innovative and interactive mathematics learning media, as well as improving the quality of mathematics learning in elementary schools.